STUDI KARAKTERISTIK MIKRO-HABITAT BURUNG MALEO (Macrocephalon maleo) PADA KAWASAN TAMAN NASIONAL RAWA AOPA WATUMOHAI (TNRAW) SULAWESI TENGGARA - Jamili, Jamili; Analuddin, Analuddin; Rudia, Adi Parman Parman (Jurnal BioWallacea, 2015)
The purpose of this study was to determine the characteristics of the bird nestingmicrohabitat hole Maleo (Macrocephalon maleo) in National Parks Aopa WatumohaiSwamp, Southeast Sulawesi . Data were collected on the savanna region block MempahoForest and savanna region Pampaea , by using descriptive method to determine the depth,temperature, pH and substrate nesting holes were found during the study . To determine thecomposition of the vegetation around the nesting hole , using roaming with 10 meters toexplore the area around the hole nesting and record the type of vegetation found. Vegetationtypes have been known to direct scientific name recorded in the field. While the type ofvegetation that is unknown scientific name, a swab or documentation then be describedfurther in the Laboratory of Ecology and Natural Sciences Taxonomy Halu Oleo Universitywith reference to the book (FLORA by Steenis, et al., 1997). The results showed the depthof hole nesting birds Maleo (Macrocephalon maleo) in the study area is 50-60 cm,temperature 28o-32oC, and soil pH of 5.9 - 7. Maleo bird nesting substrate type is dominatedby sand. Types of vegetation found around the hole nesting nesting is Melastoma sp. andKirinyuh (Eupathorium sp.), while the type of vegetation that is a place to find food andshelter includes a thorn Bamboo (Bambusa spinosa), Rao (Dracontomelon mangiferum),Banyan (Ficus spp.), Tamarind (Aleurites molucana), Caesalpinia pulcherrima, forest Mango(Mangifera sp.), Kuia (Alstonia scolaris), Nona (Metrosideros petiolata), and Bitti/Kulipapo(Vitex sp.). Total current Maleo birds encounter is as much one of the males and femaleslaying eggs on the location of the savanna region Pampaea Resort Langkowala SwampNational Park area of Rawa Aopa Watumohai Southeast Sulawesi .Keywords : Characteristics microhabitat, Bird Maleo (Macrocephalon maleo), Rawa AopaWatumohai National Park Southeast Sulawesi.